2018
DOI: 10.1002/cphc.201800610
|View full text |Cite
|
Sign up to set email alerts
|

Putting the Disulfide Bridge at Risk: How UV‐C Radiation Leads to Ultrafast Rupture of the S‐S Bond

Abstract: We investigate the ultrafast photoinduced dynamics of the cyclic disulfide 1,2-dithiane upon 200 nm excitation by time-resolved photoelectron spectroscopy and show that the S-S bond breaks on an ultrafast time scale. This stands in stark contrast to excitation at longer wavelengths where the initially excited S state evolves as the wavepacket is guided towards a conical intersection with S by a torsional motion involving a partially broken bond between the sulfur atoms. This process at lower excitation energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It is worth noticing that lower wavelengths change the picture a little and leads to decomposition in the gas phase. 72 A time-resolved X-ray study has shown that the time scale for decomposition at lower wavelengths is so long that the system is able to distribute the energy to the surrounding solvent medium. So even here the conclusions stand for what is a saving grace for the S−S bond to maintain its status as a key structural motif in biology.…”
Section: Directionality Of Internal Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noticing that lower wavelengths change the picture a little and leads to decomposition in the gas phase. 72 A time-resolved X-ray study has shown that the time scale for decomposition at lower wavelengths is so long that the system is able to distribute the energy to the surrounding solvent medium. So even here the conclusions stand for what is a saving grace for the S−S bond to maintain its status as a key structural motif in biology.…”
Section: Directionality Of Internal Conversionmentioning
confidence: 99%
“…From the crossing it is downhill all the way to the initial geometry that can then deactivate in a natural environment via the solvent molecules. It is worth noticing that lower wavelengths change the picture a little and leads to decomposition in the gas phase . A time-resolved X-ray study has shown that the time scale for decomposition at lower wavelengths is so long that the system is able to distribute the energy to the surrounding solvent medium.…”
Section: Directionality Of Internal Conversionmentioning
confidence: 99%